The role of human capital in economic growth: New results and alternative interpretations - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
While it is largely uncontroversial that human capital can be considered as one of the shaping factors of economic growth, no agreement exists on the specific role of human capital formation. Competing theories all stressing different aspects of human capital formation are not in short supply, but the empirical evidence in support of one view or another is largely missing. To be able to discriminate between alternative interpretations, it would be useful to know whether physical or human capital has a larger impact on output per capita and whether the returns to all capital are constant, increasing, or decreasing. Depending on the answers, rather different implications for the role of human capital could emerge.
More recent version: http://hdl.handle.net/10419/1647
Keywords: 330